Making visible, rendering obscure: reading the plastic crisis through contemporary artistic visual representations. (2020) - Chertkovskaya, Ekaterina; Holmberg, Karl; Petersén, Moa; Stripple, Johannes; Ullström, Sara
Non-technical summary: Modern society without plastics is difficult to imagine. Yet the global plastic system is linked to a multitude of problems of a scope that is hard to grasp and address. In short, we are facing a plastic crisis. This article explores the role of art in stimulating critical reflection about plastics and analyses how it contributes to making the plastic crisis increasingly visible. Plastic-related artworks mostly focus on ocean pollution and do not pay due attention to other aspects of the plastic crisis. At the same time, they creatively communicate clear and emotionally charged messages. Art has the potential to play an important role in coming to grips with the plastic crisis if it succeeds in adopting a broader understanding of the problem. Technical summary: Since the mid-twentieth century, plastic has become a ubiquitous material. However, its production, consumption and disposal on a massive scale have led to a range of devastating consequences that together form the 'plastic crisis'. This paper presents a novel mapping of the ways contemporary artistic visual representations narrate and politicize the plastic crisis through their different messages and aesthetics. Drawing on a multifaceted understanding of the plastic crisis and on how art navigates political and aesthetic spheres, an analysis of 35 artworks is conducted. Ocean plastic pollution emerges as a dominant theme, together with disposability; and these are connected to consumption patterns and consumer responsibility. However, less attention is given to plastic's dependence on fossil fuels and possible toxicity. The result is art of striking beauty and emotional resonance, but that downplays the systemic nature of the plastic crisis and the urgent need to hold manufacturers and regulators to account.